Performance of Islamic rural bank: maqashid sharia index - Nasution, Surayya Fadhilah (LPPM ISNJ Bengkalis, 2025)
Purpose – This study aims to explore and assess the performance of one of the Islamic rural banks in Indonesia based on the measurement of the maqashid sharia index (MSI). Method – This study relies on a quantitative descriptive approach by utilizing secondary data from the financial statements of Islamic rural banks Gebu Prima released by the FSA for 2021-2024. The method chosen to analyze this study's data is the simple additive weighting method with a multiple-attribute decision-making approach. This study uses three concepts: educating individuals, upholding justice, and promoting welfare. The MSI elements used in this study are educational grants, research, training, publicity, fair returns, functional distribution, interest-free products, profit ratio, personal income, and investment ratio in the real sector. Findings – This study's results indicate that the performance of the Islamic rural bank Gebu Prima has not been maximized because several MSI indicators have not been implemented. Implications – This research can provide insight and be a reference for future scientific studies. This research can encourage regulators to make more assertive policies related to determining performance measurement methods based on maqashid sharia so that the Islamic banking industry, such as Islamic rural banks, can improve its performance per the established guidelines.